SOCIALIZATION OF THE CHILD IN THE DIGITAL SOCIETY - Si Mohamed Louiza (International Journal of Innovative Technologies in Social Science, 2026)
Childhood is considered one of the most important stages that a human being goes through, as it is the foundation upon which their personality is built in all aspects. During this stage, the child experiences four main interconnected patterns, namely physiological, cognitive, psychological, emotional, and social development. With the emergence of the internet and the significant impacts it has had on all societies worldwide, these effects have extended to all age groups without exception. However, among the groups most affected by this advanced means of communication are children, who find themselves surrounded by a global network that provides them with everything they need, including programs, applications, electronic games, as well as information they use to complete their assignments and school research. On the other hand, there is a group of children who misuse this digital technology, which has caused them negative effects on their psychological, physical, and behavioral health. Despite this, social actors strive to find social, legal, and technical methods in order to reduce these negative effects of the internet on children.